HMGA1 silencing reduces stemness and temozolomide resistance in glioblastoma stem cells. (2nd October 2016) - Colamaio, Marianna; Tosti, Nadia; Puca, Francesca; Mari, Alessia; Gattordo, Rosaria; Kuzay, Yalçın; Federico, Antonella; Pepe, Anna; Sarnataro, Daniela; Ragozzino, Elvira; Raia, Maddalena; Hirata, Hidenari; et al.
ABSTRACT: Objective: Glioblastoma multiforme (GBM) develops from a small subpopulation of stem-like cells, which are endowed with the ability to self-renew, proliferate and give rise to progeny of multiple neuroepithelial lineages. These cells are resistant to conventional chemo- and radiotherapy and are hence also responsible for tumor recurrence. HMGA1 overexpression has been shown to correlate with proliferation, invasion, and angiogenesis of GBMs and to affect self-renewal of cancer stem cells from colon cancer. The role of HMGA1 in GBM tumor stem cells is not completely understood. Research design and methods: We have investigated the role of HMGA1 in brain tumor stem cell (BTSC) self-renewal, stemness and resistance to temozolomide by shRNA- mediated HMGA1 silencing. Results: We first report that HMGA1 is overexpressed in a subset of BTSC lines from human GBMs. Then, we show that HMGA1 knockdown reduces self-renewal, sphere forming efficiency and stemness, and sensitizes BTSCs to temozolomide. Interestingly, HMGA1 silencing also leads to reduced tumor initiation ability in vivo . Conclusions: These results demonstrate a pivotal role of HMGA1 in cancer stem cell gliomagenesis and endorse HMGA1 as a suitable target for CSC-specific GBM therapy.